Fungus-mediated synthesis of Se-BiO-CuO multimetallic nanoparticles as a potential alternative antimicrobial against ESBL-producing Escherichia coli of veterinary origin - Rasheed, Rida; Uzair, Bushra; Raza, Abida; Binsuwaidan, Reem; Alshammari, Nawaf (Frontiers in Cellular and Infection Microbiology, 2024)
Bacterial infections are emerged as a significant contributor to the mortality and morbidity worldwide. Emerging extended-spectrum beta-lactamase Escherichia coli strains provide a greater risk of bacteremia and mortality, are increasingly resistant to antibiotics, and are major producer of extended spectrum βlactamases. E. coli bacteremia-linked mastitis is one of the most common bacterial diseases in animals, which can affect the quality of the milk and damage organ functions. There is an elevated menace of treatment failure and recurrence of E. coli bacteremia, necessitating the adoption of rigorous alternative treatment approaches. In this study, Se-BiO-CuO multimetallic nanoparticles were synthesized as an alternate treatment from Talaromyces haitouensis extract, and their efficiency in treating ESBL E. coli was confirmed using standard antimicrobial assays. Scanning Electron Microscopy, UV-visible spectroscopy, and Dynamic Light Scattering were used to validate and characterize the mycosynthesized Se-BiO-CuO-Multimetallic Nanoparticles. UV-visible spectra of Se-BiO-CuO-multimetallic nanoparticles showed absorption peak bands at 570nm, 376nm, and 290nm respectively. The average diameters of the amorphous-shaped Se-BiO-CuO-Multimetallic NPs synthesized by T. haitouensis extract were about 66-80nm, respectively. Se-BiO-CuO-multimetallic nanoparticles (100μg/ml) showed a maximal inhibition zone of 18.33 ± 0.57 mm against E. coli. Se-BiO-CuO-multimetallic nanoparticles also exhibited a deleterious impact on E. coli killing kinetics, biofilm formation, swimming motility, efflux of cellular components, and membrane integrity. The hemolysis assay also confirms the biocompatibility of Se-BiO-CuO-MMNPs at MIC range. Our findings suggest that Se-BiO-CuO-multimetallic nanoparticles may serve as a potential substitute for ESBL E. coli bacteremia.